2017
DOI: 10.3389/fnmol.2017.00423
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Provides Neuroprotection through Suppressing Apoptotic, Autophagic and NF-κB-Mediated Inflammatory Pathways in a Rat Model of Recurrent Neonatal Seizure

Abstract: Interleukin-33 (IL-33) is a novel identified chromatin-associated cytokine of IL-1 family cytokines. It signals through a heterodimer comprised of ST2L and IL-1RAcp, and plays a crucial role in many diseases. However, very little is known about the role and underlying intricate mechanisms of IL-33 in recurrent neonatal seizure (RNS). To determine whether IL-33 plays an important regulatory role, we established a neonatal seizure model in this study. Rats were subjected to recurrent seizures induced by inhaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…IL-33 exerts protective and toxic bidirectional actions in many organs, depending on its doses. IL-33 induces microglia-mediated neuroinflammation also [11] , while it exhibits neuroprotection effects [ 12 , 13 ]. Moreover, IL-33 promotes microglial synapse engulfment and neural circuit development [14] .…”
Section: Introductionmentioning
confidence: 99%
“…IL-33 exerts protective and toxic bidirectional actions in many organs, depending on its doses. IL-33 induces microglia-mediated neuroinflammation also [11] , while it exhibits neuroprotection effects [ 12 , 13 ]. Moreover, IL-33 promotes microglial synapse engulfment and neural circuit development [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous literature identified that IL-33 was produced by endothelial cells and astrocytes but not by microglia or neurons, and its receptor, ST2, was mainly expressed in microglia and astrocytes cultured in vitro ( Huang et al, 2015 ). Other reports revealed that IL-33 and ST2 were mainly localized in astrocytes, microglia, and neurons, as well as oligodendrocytes after brain injury ( Jiang et al, 2012 ; Allan et al, 2016 ; Gao et al, 2017a ). Consistent with the latter, our current results showed that IL-33 was expressed at high levels in the Sham group and almost exclusively co-localized in the nucleus of oligodendrocytes, and the cytoplasm of neurons.…”
Section: Discussionmentioning
confidence: 89%
“…Noteworthily, less is known about the role and underlying mechanisms of IL-33 in the epilepsy model. Our previous studies suggested that IL-33 could exert a neuroprotective role by regulating the Bcl-2/CC-3 signaling pathway after RNS ( Gao et al, 2017a ). Consistent with previous studies, our current results revealed that IL-33 administration reduced the number of TUNEL-positive cells at 72 h post-RNS, suggesting that IL-33 processes the anti-apoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5a and b ). Recently, IL-33 was recognized as an important protector of cell survival [ 56 58 ]. In addition, it has been reported that exogenous IL-33 exhibits immunoprotective role in polymicrobial sepsis in mice by preventing early loss of T and B lymphocytes [ 59 ].…”
Section: Discussionmentioning
confidence: 99%